Lazy Susan: dumb waiting as proof of work - Crowcroft, Jon; Deegan, Tim; Kreibich, Christian; Mortier, Richard; Weaver, Nicholas (University of Cambridge, 2007)
The open nature of Internet services has been of great value to users, enabling dramatic innovation and evolution of services. However, this openness permits many abuses of open-access Internet services such as web, email, and DNS. To counteract such abuses, a number of so called proof-of-work schemes have been proposed. They aim to prevent or limit such abuses by demanding potential clients of the service to prove that they have carried out some amount of work before they will be served. In this paper we show that existing resource-based schemes have several problems, and instead propose latency-based proof-of-work as a solution. We describe centralised and distributed variants, introducing the problem class of non-parallelisable shared secrets in the process. We also discuss application of this technique at the network layer as a way to prevent Internet distributed denial-of-service attacks.